Improvement of the "Smart HCS" Platform in the Housing and Communal Services Department - F. K. Achilova (International Journal on Economics, Finance and Sustainable Development, 2022)
This article presents information about the multifunctional integrated platform "Smart housing and communal services" (smart housing and communal services), designed for management companies and manufacturers, about mobile applications interconnected with the system, web applications, online dispatch services, online payments.